Is there a correlation between cognition and the ability to remember how to use assistive devices? - Gerard Mc Carroll; Mary Cooke (Irish Journal of Occupational Therapy, 2019)
Purpose – This study aims to establish a correlation between a patient’s mini mental state examination (MMSE) score and their ability to remember how to use common assistive dressing devices. Design/methodology/approach – The study was a prospective, cross-sectional and correlational study. A final sample of 63 patients formed the study. Patients’ cognition was measured using the MMSE, and a new assessment tool was developed to assess patients’ ability to use three assistive devices and piloted on 15 patients to address normality, reliability, validity and clinical usefulness. Pearson’s rank correlation coefficient was used to establish direct correlations between the MMSE score and the assessment tool score. Eta squared was used to calculate the effect size to achieve an indication of the difference between the groups. Ethical approval had been granted by the regional ethics committee. The null hypothesis states that patients with an MMSE score of 22 or less show no difference in their ability to safely and appropriately use assistive devices provided and demonstrated by an occupational therapist than patients with an MMSE score of 23 or higher. Findings – The null hypothesis was rejected and patients with an MMSE score of 22 or less showed a significant difficulty in their ability to use the three devices. Correlation coefficients showed significant positive correlations between MMSE scores and assistive devices scoring tool results for all three devices: Helping hand (r = 6.677, n = 60, p = 0.01), shoe horn (r = 0.649, n = 54, p = 0.01) and sock aid (r = 0.877, n = 54, p = 0.01). Originality/value – The study is in an Irish context and demonstrated primary, objective evidence of the impact of impaired cognition on functional ability. Patients with cognitive deficits pose a larger safety challenge but still should be afforded an opportunity to use and benefit from assistive devices. The assessment tool is a new and unique instrument and although requires further development, may conceivably act not just as an assessment instrument but also an effective treatment tool.